South-South migration and human development - Bakewell, O (International Migration Institute, 2009)
This paper looks at the relationship between migration between developing countries – or countries of the global ‘South’ – and processes of human development. The paper offers a critical analysis of the concept of South-South migration and draws attention to four fundamental problems. First, there is no clear definition of the boundaries between 'South' and 'North' and different organisations place different countries in different categories. Second, migration systems tend to cut cross such boundaries, wherever they are place. Third, there is no analytical basis for distinguishing between 'South' and 'North'; hence there is no rationale for assuming that South-South migration should be any different from South-North or North-North migration. Fourth, the available definitions of South and North change over time, creating difficulties for any longitudinal analysis. Having highlighted these problems, the paper then gives a broad overview of the changing patterns of migration in developing regions, with a particular focus on mobility within the African continent. It outlnes some of the economic, social and political drivers of migration within poor regions, noting that these are also drivers of migration in the rest of the world. It also highlights the role of the state in influencing people's movements and the outcomes of migration. The paper highlights the distinctive contribution that migration within developing regions makes to human development in terms of income, human capital and broader processes of social and political change. The paper concludes that the analysis of migration in poorer regions of the world and its relationship with human development requires much more data than is currently available. This should focus on understanding the role of migration (and mobility) in the lives of the poor. It is important to develop a much more sophisticated analysis of the differences in migration patterns across the world than that which can be achived by simply dividing the world into crude blocks of 'South' and 'North'.